Role stress among auxiliary nurses midwives in Gujarat, India. Issue 1 (December 2017) - Purohit, Bhaskar; Vasava, Paul
Abstracts Background Understanding Role Stress is important as health service providers, especially nurses experience high levels of Role Stress which is linked to burnout, poor quality of care and high turnover. The current study explicates the concept of Role Stress and assesses the Role Stress experienced by the Auxiliary Nurse Midwives (ANMs) working with rural government health centres from Gujarat, India. Methods The study included 84 ANMs working with government health centres from one district in India. A structured instrument with established reliability and validity was used to measure 10 dimensions of Role Stress namely: Inter-role distance, role stagnation, role expectation conflict, role erosion: role overload, role isolation, personal inadequacy, self-role distance, role ambiguity and resource inadequacy. The study instrument was based on 5 point Likert rating scale that contained 50 unidirectional negative statements, 5 for each dimension. Kolmogorov-Smirnov and Shapiro-Wilk test were carried out to assess if the data were normally distributed. Cronbach's alpha test was carried out to assess reliability of the instrument. The study data was analyzed using descriptive statistics mainly using mean scores with higher scores indicating higher Role Stress and vice versa. The data was analyzed using SPSS version 19. Results Kolmogorov-Smirnov and Shapiro-Wilk test indicated that the data were normally distributed. Cronbach's alpha test indicated values of 0.852 suggesting high reliability of the tool. The highest Role Stress among ANMs was experienced for resource inadequacy. Role overload, role stagnation and inter-role distance were among the other important role stressors for ANMs. The study results suggests that ANMs frequently feel that: they do not have adequate amount of resources, facilities and financial support from the high levels authorities; people have too many expectations from their roles and as result they are overloaded with work and have very limited opportunities for future growth. Conclusion The current study has the potential to provide a useful and a comprehensive framework to understand the Role Stress among the health service providers that could be further useful in designing interventions specifically aimed at reducing Role Stress in order to prevent burnout thereby addressing the productivity and retention.